A contribuição da disciplina Jogos de Empresas na formação de alunos do curso de Ciências Contábeis da Universidade do Estado de Mato Grosso - Unemat - Silva, Paulo Roberto Pimenta da (Universidade do Vale do Rio dos Sinos, 2013)
The aim of this study is to describe the contribution of the business games subject in the academics formation of the Accounting Sciences at the State of Mato Grosso University – UNEMAT, at Sinop, Tangará da Serra and Cáceres campuses. This is a research of applied nature, using qualitative and descriptive approach and technical procedure survey with questions raised with students at the beginning of the second semester of 2012 from the 7th semester in Sinop and 6th semester in Tangará Serra, and at the end of second semester of 2012 students from the 6th, 7th and 8th semesters in Tangará da Serra, in a total of 104 students. Two teachers who are in charge of the subject and the course coordinator in Cáceres, where the subject isn’t offered yet, were also interviewed. From the academics point of view, the results achieved indicate the business games subject contributed to aggregate knowledge by allowing them to experience situations that happen in the companies, allowing them a professional performance with higher quality. The professors who were interviewed emphasize the contribution of the subject to form a professional who is more oriented to management, to empower the academics to assess the impacts of decision making, to strengthen their relationships through the group activities, and to qualify the teaching in the accounting area.
Keywords: Jogos de empresa; Tomada de decisão; Gestão de negócio; Business games; Decision making; Business management; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis